IMPACT OF FLIPPED CLASSROOM IN GENERIC STUDENTS IN COLLEGE OF NURSING, NISHTAR MEDICAL UNIVERSITY MULTAN - SHAUKAT , N; NISA , QR; ISMAIL , R (Biological and Clinical Sciences Research Journal, 2024)
Traditional teaching methods in nursing education often fail to engage students in active learning, limiting their ability to develop critical thinking and problem-solving skills. The flipped classroom model, which integrates pre-class independent learning with in-class active engagement, has shown promise in improving learning outcomes. Objective: To evaluate the impact of the flipped classroom model on academic performance, engagement, and perceptions among nursing students at the College of Nursing, Nishtar Medical University, Multan. Methods: A quasi-experimental pre-test and post-test design was used. A total of 130 BSN students were randomly assigned to experimental (flipped classroom) and control (traditional lecture) groups. Pre-class materials were provided to the experimental group, while the control group followed traditional lectures. Data were collected using a validated questionnaire and analyzed using IBM SPSS version 26. Results: The flipped classroom model significantly improved post-test scores, critical thinking, and engagement levels compared to traditional methods. Most students (85%) reported that the flipped classroom approach fostered lifelong learning skills, and 90% agreed it effectively integrated theory and practice. Key challenges included limited resources and infrequent use of flipped learning by educators. Conclusion: The flipped classroom model is an effective strategy for enhancing academic performance and engagement in nursing education. Addressing barriers such as faculty training and resource limitations is essential for its successful implementation in resource-constrained settings like Pakistan.